The Relationship between Knowledge and Attitudes of Pregnant Women Regarding Preparation for Childbirth (Labor Pain) in the Independent Practice of Midwife Hellen Tarigan in 2022 - Sitepu, Jujuren Br.; Mengkuji, Betty; Silaban, Natalia (Formosa Journal of Applied Sciences, 2024)
The maternal mortality rate (MMR) will be 70 per 100,000 live births in 2030. The maternal mortality rate (MMR) in the world is 303,000 people. The maternal mortality rate (MMR) according to WHO is 295,000 per 100,000 live births, women dying during pregnancy and childbirth in 2017. This number is still relatively high, one of the causes of maternal death in the world, namely bleeding during childbirth. The research design used is descriptive research. The population in the study was 30 respondents with a sample of 30 respondents taken using total sampling techniques. There is a significant relationship between the knowledge of pregnant women and preparation for childbirth, with a p-value (0.000 < 0.005) and there is a relationship between the attitude of pregnant women and preparation for childbirth with a p-value (0.001 < 0.005). It is hoped that health workers can provide counseling about preparation for childbirth to pregnant women when carrying out Ante Natal Care (ANC) at PMB.